Cannabinoids and the endocannabinoid system in reward processing and addiction: from mechanisms to interventions - Spanagel, Rainer (Dialogues in clinical neuroscience, 2020)
The last decades have seen a major gain in understanding the action of cannabinoids and the endocannabinoid system in reward processing and the development of addictive behavior. Cannabis-derived psychoactive compounds such as Δ9-tetrahydrocannabinol and synthetic cannabinoids directly interact with the reward system and thereby have addictive properties. Cannabinoids induce their reinforcing properties by an increase in tonic dopamine levels through a cannabinoid type 1 (CB1) receptor-dependent mechanism within the ventral tegmental area. Cues that are conditioned to cannabis smoking can induce drug-seeking responses (ie, craving) by eliciting phasic dopamine events. A dopamine-independent mechanism involved in drug-seeking responses involves an endocannabinoid/glutamate interaction within the corticostriatal part of the reward system. In conclusion, pharmacological blockade of endocannabinoid signaling should lead to a reduction in drug craving and subsequently should reduce relapse behavior in addicted individuals. Indeed, there is increasing preclinical evidence that targeting the endocannabinoid system reduces craving and relapse, and allosteric modulators at CB1 receptors and fatty acid amide hydrolase inhibitors are in clinical development for cannabis use disorder. Cannabidiol, which mainly acts on CB1 and CB2 receptors, is currently being tested in patients with alcohol use disorder and opioid use disorder.